2023
DOI: 10.1002/tox.23966
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and zinc alleviate hepatotoxicity induced by heavy metal mixture (cadmium, mercury, lead and arsenic) via attenuation of inflammo‐oxidant pathways

Harrison Ozoani,
Anthonet N. Ezejiofor,
Kenneth O. Okolo
et al.

Abstract: Heavy metals (HM) are believed to be injurious to humans. Man is exposed to them on daily basis unknowingly, with no acceptable protocol to manage its deleterious effects. These metals occur as mixture of chemicals with varying concentrations in our atmosphere. There are growing calls for the use of essential metals in mitigating the injurious effects induced by heavy metals exposure to man; therefore, the aim of this study was to evaluate the protective effects of essential metals (Zinc and Selenium) in a mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
(201 reference statements)
0
2
0
Order By: Relevance
“…14 Additionally, consuming a combination of important nutrients such as zinc and selenium may help alleviate liver damage caused by a mixture of heavy metals such as Cd, mercury, Pb, and As, by reducing inflammation and oxidative pathways. 15 Furthermore, selenium has been found to mitigate oxidative stress induced by Cd. 16 Previous research has indicated that incorporating trace elements into one's diet could serve as an alternative approach for managing T2DM, and has the potential to alter the inflammatory profile.…”
Section: Introductionmentioning
confidence: 99%
“…14 Additionally, consuming a combination of important nutrients such as zinc and selenium may help alleviate liver damage caused by a mixture of heavy metals such as Cd, mercury, Pb, and As, by reducing inflammation and oxidative pathways. 15 Furthermore, selenium has been found to mitigate oxidative stress induced by Cd. 16 Previous research has indicated that incorporating trace elements into one's diet could serve as an alternative approach for managing T2DM, and has the potential to alter the inflammatory profile.…”
Section: Introductionmentioning
confidence: 99%
“…Selenium nanoparticles (SeNPs) have emerged as a potential alternative to implantable coatings, as they promise to mitigate the toxicity of metallic biomaterials [ 22 , 23 ]. They exhibit low toxicity, although high doses may still hinder cell proliferation and function [ 24 ].…”
Section: Introductionmentioning
confidence: 99%